2008
DOI: 10.1007/s00213-007-1063-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of the α7 nicotinic partial agonist, S 24795, and the cholinesterase inhibitor, donepezil, against aging-related deficits in declarative and working memory in mice

Abstract: This preclinical demonstration that S 24795 restored specific age-related memory deficits with as much efficacy as donepezil adds to recent literature in highlighting the potential interest of an alpha7 nAChR drug as a symptomatic AD therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 71 publications
2
28
0
Order By: Relevance
“…We show that by removing A␤ 42 from existing A␤ 42 -␣7nAChR complexes, S 24795 reinvigorates ␣7nAChRs and NMDARs, two prominent synaptic modulators. Hence, S 24795 may achieve a therapeutic effect in AD by combating A␤ 42 -mediated ␣7nAChR and NMDAR suppression (Beracochea et al, 2008;Marighetto et al, 2008). Additionally, S 24795 may promote synaptic LTP by directly activating A␤-free ␣7nAChRs to augment NMDAR function (Lagostena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that by removing A␤ 42 from existing A␤ 42 -␣7nAChR complexes, S 24795 reinvigorates ␣7nAChRs and NMDARs, two prominent synaptic modulators. Hence, S 24795 may achieve a therapeutic effect in AD by combating A␤ 42 -mediated ␣7nAChR and NMDAR suppression (Beracochea et al, 2008;Marighetto et al, 2008). Additionally, S 24795 may promote synaptic LTP by directly activating A␤-free ␣7nAChRs to augment NMDAR function (Lagostena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that the ␣7nAChR-specific agonists and partial agonists enhance learning and memory in animal models of cognitive deficits (Pichat et al, 2007;Beracochea et al, 2008;Marighetto et al, 2008). However, it is not clear how the existing A␤ 42 -␣7nAChR complexes are affected by the ␣7nAChR…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized a wide range of pharmacological doses of donepezil in order to improve behavior in mice (e.g., Spowart-Manning and van der Staay 2004; Csernansky et al 2005;Dong et al 2005;Riedel et al 2009). However, treatment of donepezil using a 0.3 mg/kg dose has been shown to reverse behavioral deficits in middle-aged mice completing an episodic contextual memory task (Béracochéa et al 2007), improve Morris Water Maze performance in a APP23 mutant mouse model of AD (Van Dam et al 2005), and improve shortterm working memory in aged mice (Marighetto et al 2008). Pirenzepine (0.02, 0.2, and 2.0 mg/kg) was also given to these animals in a crossed Latin square design; however, there were no effects of this drug (data not shown), likely due to its suspected inability to cross the blood-brain barrier (Piper 1995).…”
Section: Pharmacological Challengesmentioning
confidence: 99%
“…Many companies are now exploring potential cognitive enhancers in AD transgenics, such as a7 agonists (Marighetto et al 2008), phosphodiesterase inhibitors (Puzzo et al 2009;Verhoest et al 2009), H3 antagonists (Medhurst et al 2007), and other approaches. Perhaps targeting cognitive decline in the presence of pathology will be more successful than targeting the pathology alone, which has been the trend of the past decade, or using a combination approach.…”
Section: Translational Issuesmentioning
confidence: 99%